Moral norms and physical necessity: Zhu Xi on the concept of Li - Yuksel, Diana (Acta Orientalia Vilnensia, 2007)
The aim of this paper is to analyze one of the key concepts in Zhu Xi’s thought，Li 理，from the perspective of Confucian ethics and to stress its importance in the strategic synthesis of Confucian thought realized by Zhu Xi in the 12th century. Focusing on the fundamental concepts of Neo-Confucian thought—Li (principle), Qi 氣 (vital force), Dao 道 (the way/nature), Ren 仁 (humanity) and Xin 心 (mind-heart)—the paper turns its attention to the inseparability of metaphysical and ontological perspectives on the one hand, and, on the other hand, the ethical perspective in the new Confucian paradigm. Taking into consideration the various definitions given to the concept Li, this paper attempts an interpretation of the concept based on the ineluctability of the Confucian moral norms stated by Zhu Xi, according to which in the order of the world everything happens under the unavoidable sign of the necessity of its issuance. These findings suggest that Li is a concept composed of a sum of various aspects (li) resulting from the different instances of its issuance in the world with which the mind-heart governed by it is confronted, therefore proving that Li is the sum of moral norms that encompass humanity, righteousness, rites and wisdom, the pillars of the Confucian moral order.